Efeito do cinamaldeído sobre o metabolismo de nucleotídeos e nucleosídeo da adenina e em modelo experimental em artrite por adjuvante - Thorstenberg, Maria Luiza Prates (2014)
Rheumatoid arthritis (RA) is a chronic, multisystem inflammatory disease with autoimmune features evident, expressing a cellular response of Th1. Characterized primarily by chronic synovitis, erosive and symmetrical, preferably peripheral joints, where there is an intense inflammatory process. The purinergic signaling system plays an important role in the modulation of inflammatory and immune responses through extracellular biomolecules such as nucleotides adenine and adenosine derivative nucleodise therefore, which are essential to providing the trigger and maintain the trigger inflammatory response. The effects of these molecules are promoted by the action of purinergic receptors specific and controlled by ectoenzymes, in cell surface. Based on these principles, this study investigated the effect of cinnamaldehyde in thermal hyperalgesia, , arthritis score, paw edema and thermal hyperalgesia as well histolgical parameters beyond the activity of the E-NTPDase and E-ADA in lymphocytes in rats adjuvant arthritis. The rats were divided in four groups, of wich two were adjuvant induced arthritis in the other two control groups. The animal received the compound at a concentration of 2,1% orally for a period of 15 days. Not differences were observed among analysis the arthritis score, paw edema it is however noted differences in thermal hyperalgesia in about 60% and in group induced arthritic and treated with cinnamaldehyde. Compared histological analysis it was noticed a slight reduction the lynphocitytic inflammatory infiltration in rats induced arthritis and treated with cinnamaldehyde. We found the increased the ATP hydrolysis in about 94,14% in arthritis induced when compared with control group and 20,58% when compared with groups treated with cinnmaldehyde . However, E-NTPDase activity when used ADP as substrate rised in 152,56% in relation the control group and 122,76% in relation the control group treated with cinnamaldehyde. In E-ADA activity was observed the increased in about 151,84%%in group arthritis induced when compared with control groups and rise 69,7% when compared with group arthritis induced treated with cinnamakdehyde. In conclusion, the data indicate that cinnamaldehyde was able to reduce thermal hyperalgesia and alterations histological in rats induced arthritis, as well as decreased the ectonucleotidase cascade, once we observed a activity gradual decrease in lymphocytes in group induced arthritis and treated with cynnamaldehyde in relation with all others groups. Therefore cinnamaldehyde was act to skewing some effects inflammatory of induced arthritis. Although requiring further study, cinnamaldehyde could be used as a complementary fot the benefit of people with rheumatoid arthritis.